2018
DOI: 10.1016/j.cgh.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Colonoscope Distal Attachment Devices in Increasing Rates of Adenoma Detection: A Network Meta-analysis

Abstract: Based on network meta-analysis, we anticipate only modest improvement in ADRs with use of distal attachment devices, especially in low-performing endoscopists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
74
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 51 publications
5
74
1
1
Order By: Relevance
“…Conversely, in 35% < ADR < 45% and ADR > 45%, EAC appeared no benefits over SC. Thus it can be concluded that EndoCuff may be more helpful for operators with a low level rather than a high level of ADR, which was consistent with the previous studies . Operators with low level of ADR are mainly trainees or endoscopists with poor operating habits (eg, withdrawing too quickly or not observing carefully) who may easily miss the lesions hiding behind folds and large curves of flexures.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Conversely, in 35% < ADR < 45% and ADR > 45%, EAC appeared no benefits over SC. Thus it can be concluded that EndoCuff may be more helpful for operators with a low level rather than a high level of ADR, which was consistent with the previous studies . Operators with low level of ADR are mainly trainees or endoscopists with poor operating habits (eg, withdrawing too quickly or not observing carefully) who may easily miss the lesions hiding behind folds and large curves of flexures.…”
Section: Discussioncontrasting
confidence: 62%
“…Three meta‐analyses have been performed to confirm the effect of EndoCuff . Fewer studies were included in the early meta‐analysis, and most of these articles were of low quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A network meta-analysis by Facciorusso et al reported that distal attachment devices, including caps, Endocuff, and EndoRings, increased ADR compared with SC (relative risk, 1.13; 95% confidence interval, 1.03-1.23), with low-quality evidence. 38 A meta-analysis of EAC versus SC including four randomized controlled trials, four retrospective cohort studies, and one prospective observational study showed that the ADR was significantly higher in the EAC group than in the SC group. 31 Another recent meta-analysis of EAC versus SC including 12 randomized controlled trials showed that the ADR and polyp detection rate were significantly higher in the EAC group than in the SC group, and the MAP tended to be higher with EAC.…”
Section: Discussionmentioning
confidence: 99%
“…However, larger multicenter randomized controlled trials (RCT) have not shown a consistent benefit for enhanced adenoma detection 1 and a further study has shown ADR to be numerically worse with EAC. 2 Faccioruso et al 3 performed a network metanalysis of 25 different RCTs comparing add-on devices with ADR as the primary endpoint. This analysis found a modest advantage for EAC over standard colonoscopy (low quality evidence).…”
mentioning
confidence: 99%